Beyond the nation-state - Kamens, David H. (Bingley, U.K. : Emerald, 2012)
The book examines the effects of education in creating global citizens who share a world culture. This occurs within an international system that still remains decentralized, composed of independent nation-states as major actors. Prof. Kamens argues that as globalization intensifies, this system of nation-states becomes more saturated and dense with structure. Intensified globalization has produced a world society, thanks to the spread of global capitalism, education, democracy and bureaucracy. The upshot is that world culture travels quickly and produces recipes for the development of an imagined community that has increasing commonalities across societies. The book examines the role of education in diffusing such attitudes and models, as global citizens confront national institutions.
ch. 1. The world polity and political culture / David H. Kamens -- ch. 2. 'Knowledge societies', agency, and new actors / David H. Kamens -- ch. 3. Individualism and its institutional consequences / David H. Kamens -- ch. 4. States without nations : reconstructing society / David H. Kamens -- ch. 5. Modernity and changing patterns of intolerance / David H. Kamens -- ch. 6. New models of nationhood and citizenship / David H. Kamens -- ch. 7. 'Global citizens' and national institutions / David H. Kamens -- ch. 8. New polities, new standards for political elites / David H. Kamens -- ch. 9. The construction of public opinion / David H. Kamens -- ch. 10. The media : the decline of credibility and elite control / David H. Kamens -- ch. 11. The future of nationhood / David H. Kamens.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Sociology -- General; Education -- Philosophy & Social Aspects; Sociology; Globalization; Education and globalization; Nation-state.